Regulation of the Education Rights of Persons with Disabilities in Law Number 8 of 2016 concerning Persons with Disabilities - Maharani Nurdin (LEGAL BRIEF, 2022)
As citizens of Indonesia, persons with disabilities constitutionally have the same rights and positions before the law and the government. The state should be directly involved in people's welfare efforts, such as directly providing various forms of basic services, such as education services. The 1945 Constitution guarantees in each of its articles that every citizen has the right to get facilities and special treatment to obtain equal opportunities and benefits in order to achieve equality and justice, so that welfare will be formed for all citizens, have the right to protection from violence and discrimination. . Law Number 8 of 2016 concerning Persons with Disabilities regulates the right to education for persons with disabilities, providing an understanding that Persons with Disabilities need certain treatment, certain treatments, certain facilities, which are then tried to be explained and regulated further in the Law This basically refers to the Convention On The Rights Of Persons with Disabilities which has been ratified in Law Number 19 of 2011.